Amalgamation between the Yangtze and Cathaysia Blocks in South China: Constraints from SHRIMP U-Pb zircon ages, geochemistry and Nd-Hf isotopes of the Shuangxiwu volcanic rocks - Li, X.; Li, W.; Li, Zheng-Xiang; Lo, C.; Wang, J.; Ye, M.; Yang , Y. (Elsevier Science BV, 2009)
South China was formed through the amalgamation of the Yangtze Block with the Cathaysia Block, but the timing of this amalgamation is controversial, ranging from Mesoproterozoic to Mesozoic. We report here SHRIMP U-Pb zircon ages, geochemistry and Nd-Hf isotopes of the Shuangxiwu Group volcanic rocks from the southeastern Yangtze Block. These rocks were strongly deformed, metamorphosed to greenschist-facies, intruded by 8497Ma dolerites, and unconformably overlain by Neoproterozoic rift successions of no older than ca. 820 Ma. The Beiwu and Zhangcun volcanic rocks from the middle and uppermost Shuangxiwu Group were dated at 92615Ma and 89112 Ma, respectively. All the studied rocks are characterized by highly positive ENd(T) (5.4-8.7) and EHf(T) (11.0-15.3) values. The Pingshui basaltic and andesitic rocks from the lower Shuangxiwu Group, which were previously dated at ca. 970 Ma, are high in Al2O3 (15-20%) but low in MgO (>8%), and are characterized by enrichments in Th and LREE but depletions in Nb, Ta, Zr, Hf and Ti, broadly similar to high-Al basaltic rocks in many volcanic arcs. The Beiwu andesitic to rhyolitic rocks have higher MgO than the experimental melts of basaltic rocks, and their Al2O3 content decreases with increasing SiO2, similar to the regional coeval tonalites and granodiorites, suggesting their formation by crystal fractionation of basaltic parent magma. The Zhangcun volcanic rocks are high in SiO2 (mostly >69%), low in MgO (0.35-1.2%), and have nearly constant Al2O3 contents of 14-15% and relatively uniform trace element concentrations. They were generated by remelting of juvenile mafic to intermediate arc rocks. Overall, the Shuangxiwu Group volcanic rocks and associated intrusive tonalites and granodiorites constitute a typical calc-alkaline magmatic assemblage of a 970-890 Ma active continental margin. These results and the 8497Ma zircon U-Pb age for the undeformed doleritic dikes intruding the Shuangxiwu Group suggest that the tectonic regime of the study region transformed from plate convergence to intracontinental rifting in the time period between ca. 890Ma and ca. 850 Ma. Previously reported 1.04-0.94Ga metamorphic and deformation ages from the nearby Tianli Schists and evidence for the final closure of the back-arc basin at ca. 880Ma (ophilitic obduction at Xiwan), further suggest that the amalgamation between the Yangtze and Cathaysia Blocks, likely through 'soft docking' at the eastern segment of the Sibao orogen, was completed at ca. 880Ma or soon after.